AB0354 STEPPING UP FOR INFLAMMATORY ARTHRITIS: A PILOT TRIAL TO TEST BEHAVIORAL ECONOMICS STRATEGY TO INCREASE PHYSICAL ACTIVITY IN INFLAMMATORY ARTHRITIS. (2nd June 2020) - Ogdie, A.; Patel, M.; Curtis, J.; Gavigan, K.; Nowell, W. B.; Baker, J.
Abstract : Background: Regular physical activity may have benefits for patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA), but patients with active disease are often reluctant to increase activity. Principles from behavioral economics (BE), a field combining psychology and economics, have been applied to motivate increased physical activity in non-arthritis patients. 1 No published studies have examined the application of BE concepts in rheumatology to promote exercise. Objectives: To assess the feasibiility and efficacy of a loss aversion financial incentive for increasing step counts and improving disease symptoms in RA and PsA patients with active disease. Methods: A randomized controlled pilot trial was performed among patients with RA and PsA. Participants were required to have active disease defined by having at least one swollen joint and a Routine Assessment of Patient Index Data-3 (RAPID3) score>3 (range 0-30 with <3 indicating remission). The trial included two visits (baseline and 14-week) and weekly check-ins via virtual trial platforms, Way to Health and the ArthritisPower app. Patients were given a Fitbit Alta at baseline and completed a two-week run-in period to assess average step count. Patients were then prompted to select a step count goal and complete a commitment contract. After selection of a goal, participants randomized to the intervention arm received a financial loss aversion incentive (each month, patients started with $75 in their account and lost $2.50 for each day they did not reach their goal). Patients were blinded to the other study arm and investigators were blinded to assignment. All patients received weekly text message prompts providing feedback about their performance over the previous week, completed weekly PROs, and had the opportunity to report adverse events including flares of joint pain. After 12 weeks of the intervention (at week 14), the incentive was removed and patients were followed to 26 weeks to determine how long the effect persisted. Results: In the pilot trial, 71 patients were verbally consented for screening, 34 underwent screening (of these, two were ineligible), 27 were randomized, and 22 patients completed the 14-week study visit. Mean age of participants was 50 (SD 13), 85% were female, 17(63%) had PsA, mean BMI was 30.6 and mean swollen (0-66) and tender (0-68) joint counts were 6.2 (5.6) and 8.1 (9.1), respectively. Baseline RAPID3 was 10.5 (SD 4.6) and the mean step count at baseline was 5, 962. By 28 days, 65% of patients increased their step count. Participants receiving the incentive had an average of 714 more steps per day over the first 14 weeks and a greater probability of reaching 10, 000 steps per day during follow-up (30% v. 21%, p=0.41). Among patients who achieved their step count goals more than 50% of days, we observed more improvement in sleep quality, fatigue, and overall well-being (p<0.05) (Figure 1 ). After adjusting for baseline RAPID3, the 14-week RAPID3 scores were lower in the group that achieved their step goals 50% of the time [B: -3.91 (-11.8, 3.99); a difference that approximates the minimal clinically important difference (MCID) for the RAPID3 (3.6). Conclusion: While financial incentives have worked well in patients without arthritis, the estimated effect of the financial incentive in this small study was more modest in patients with RA and PsA. Those that were able to increase their physical activity and meet their step goals had greater improvements in symptoms over the course of the study. These data support further study in this area to promote physical activity by leveraging concepts from behavioral economics. References: [1]Ogdie & Asch. Nat Rev Rheumatol. 2019 Disclosure of Interests: Alexis Ogdie Grant/research support from: Pfizer, Novartis, Consultant of: Abbvie, Amgen, BMS, Celgene, Corrona, Janssen, Lilly, Pfizer, Novartis, Mitesh Patel Shareholder of: Owner, Catalyst Health LLC, Consultant of: Advisory Board Member for Healthmine Services, Life.io, Holistic Industries, Jeffrey Curtis Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Corrona, Janssen, Lilly, Myriad, Pfizer, Regeneron, Roche, UCB, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Corrona, Janssen, Lilly, Myriad, Pfizer, Regeneron, Roche, UCB, Kelly Gavigan: None declared, W. Benjamin Nowell: None declared, Joshua Baker: None declared